Perception, Expectation, Affect, Analysis - Elizabeth Hellmuth Margulis (Zeitschrift der Gesellschaft für Musiktheorie)
Descriptive music analysis often aims to explain musical experience in terms of the characteristics of musical structure. But musical experience is largely subjective and varies from listener to listener. This paper uses a case study of expectation theory to demonstrate how sensitive analysis can account for commonalities in musical experience while reserving space for individual differences. The account relies on previous empirical work establishing that topical context can modulate the kind of affect generated by a syntactic surprise. According to this model, surprise generates perceived intensity broadly across experienced listeners, but the topical context helps select the dimension along which the intensity gets perceived. By teasing apart these mechanisms, a clearer delineation of which aspects of experience might be shared across listeners and which are more susceptible to individual differences can be established.